The native data and native qualities of Mongolians - Sanduijav, Odkhuu (Studia Philosophiae Et Juris, 2024)
Each country has different mindsets, images, behaviors, and internal facts that come from its existence, its active economy, its traditional lifestyle, its daily lifestyles, and its intrinsic facts. Many factors contribute to the disintegration and unification of Mongolians, including, without limitation, living conditions, income, language and culture, mentality, traditions and inheritance, habits, behaviors and characteristics, personalities, ways of life, appearance and body, image, mentality, attitudes and trends. All these characteristics attract both foreigners and researchers. We also bring together and globalize through various features. We will talk about several characteristics that separate, disintegrate and separate Mongolians from other countries. Монголчуудын төрөлх өгөгдөл, унаган чанар Хураангуй: Монголчуудын үндэсний сэтгэлгээний шинж төрх, зан араншин нь бидний язгуур соёл, амьдралын хэв маяг, шашин шүтлэг гаднынхтай холилдоогүй харьцангуй цэвэр, дангаараа байсан эрт дээр үед хоногшин тогтож, төлөвшин хөгжиж ирсэн онцлогтой. Монголчууд сүүлийн 3 зууны хугацаанд харь гүрний эрхшээлд, оюун санааны эрх чөлөөгөөр гачигдаж ирсэн учир улс төр, үзэл суртлын болон соёл шашны нөлөөнд автах, манжжуулах, хятаджуулах, оросжуулах, баруунжуулах алсын зорилго, далд бодлогын туршилтын талбар болж ирсэн гашуун сургамж бий. Харийн бодлого, гаднын нөлөөний үр дүнд бидний монголчууд унаган шинж төрх, үндсэн зан, үндэсний онцлогоо ямар нэг байдлаар гээж, бүдгэрэн балартаж, “олдмол” маягийн зан чанартай болсон нь нууц биш, бас түүхийн үнэн юм. Tүлхүүр үгс: мэргэн ухаан, аз жаргал, баяр баясгалан, төгс сайхан